2018
DOI: 10.1021/acscatal.7b02165
|View full text |Cite
|
Sign up to set email alerts
|

Facile Ammonia Synthesis from Electrocatalytic N2 Reduction under Ambient Conditions on N-Doped Porous Carbon

Abstract: Ammonia has been used in important areas such as agriculture and clean energy. Its synthesis from the electrochemical reduction of N 2 is an attractive alternative to the industrial method that requires high temperature and pressure. Currently, electrochemical N 2 fixation has suffered from slow kinetics due to the difficulty of N 2 adsorption and NN cleavage. Here, N-doped porous carbon (NPC) is reported as a cost-effective electrocatalyst for ammonia synthesis from electrocatalytic N 2 reduction under ambie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
400
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 532 publications
(407 citation statements)
references
References 34 publications
6
400
0
1
Order By: Relevance
“…for pristine Bi 4 V 2 O 11 and BVC-C,respectively.Inmarked contrast, CeO 2 only shows trace amount NH 3 production, which elucidates that Bi 4 V 2 O 11 phase is the core component in BVC-A hybrid catalyst and the electron transfer direction accords with the illustration shown in Figure 2i.A bove inference can be further affirmed by the decrease of NH 3 yield in BVC-A-2 (Ce/Bi = 1.5) and BVC-A-3 (Ce/Bi = 1) with less mole ratios of Bi 4 V 2 O 11 (Supporting Information, Figure S21). [48] In summary,anoble-metal-free BVC-A hybrid containing amorphous Bi 4 V 2 O 11 is fabricated via as ingle spinneret electrospinning with subsequent calcination approach. Thec orresponding UV/Vis absorption spectra are exhibited in Figure 3d.The clear difference reveals that the amorphous Bi 4 V 2 O 11 serve as active ingredients in as-constructed hybrid catalyst, while the CeO 2 serves as the trigger to induce amorphous structure as well as the partner to establish band alignment for charge transfer.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…for pristine Bi 4 V 2 O 11 and BVC-C,respectively.Inmarked contrast, CeO 2 only shows trace amount NH 3 production, which elucidates that Bi 4 V 2 O 11 phase is the core component in BVC-A hybrid catalyst and the electron transfer direction accords with the illustration shown in Figure 2i.A bove inference can be further affirmed by the decrease of NH 3 yield in BVC-A-2 (Ce/Bi = 1.5) and BVC-A-3 (Ce/Bi = 1) with less mole ratios of Bi 4 V 2 O 11 (Supporting Information, Figure S21). [48] In summary,anoble-metal-free BVC-A hybrid containing amorphous Bi 4 V 2 O 11 is fabricated via as ingle spinneret electrospinning with subsequent calcination approach. Thec orresponding UV/Vis absorption spectra are exhibited in Figure 3d.The clear difference reveals that the amorphous Bi 4 V 2 O 11 serve as active ingredients in as-constructed hybrid catalyst, while the CeO 2 serves as the trigger to induce amorphous structure as well as the partner to establish band alignment for charge transfer.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[1][2][3][4] From an energy-saving perspective,g reen N 2 to NH 3 fixation methods are strongly desired because the main industrial process for producing NH 3 -the Haber-Bosch process-requires extremely harsh reaction conditions (400-600 8 8C, 20-40 MPa) and causes pollution and greenhouse gas emissions. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] However,t he efficiency of the NRR suffers from ap arallel hydrogen evolution reaction (HER) in aqueous solutions on traditional NRR electrocatalysts. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] However,t he efficiency of the NRR suffers from ap arallel hydrogen evolution reaction (HER) in aqueous solutions on traditional NRR electrocatalysts.…”
mentioning
confidence: 99%
“…[12][13][14][15] To this end, the search for an electrocatalytic NRR center in recent years has mainly focused on transition-metal-based materials. [27][28][29][30][31] Fore xample, Yu et al reported ah igh NH 3 production rate and faradaic efficiency by using boron-doped graphene as am etal-free NRR catalyst under ambient conditions. [7] It is worthwhile to note that although an unoccupied nonbonding orbital and electron donor site with abundant electron cloud density are prerequisites for aN RR catalyst, the do rbital electrons in transition metals also benefit the formation of metal-hydrogen bonds,w hich will exacerbate the competitive hydrogen evolution reaction and limit the nitrogen reduction selectivity and catalytic efficiency.…”
mentioning
confidence: 99%
“…[24] Compared to transition metals,t he weak hydrogen adsorption of nonmetallic elements and their abundant valence electrons should provide am ore ideal nitrogen activation center. [27][28][29][30][31] Fore xample, Yu et al reported ah igh NH 3 production rate and faradaic efficiency by using boron-doped graphene as am etal-free NRR catalyst under ambient conditions. [27][28][29][30][31] Fore xample, Yu et al reported ah igh NH 3 production rate and faradaic efficiency by using boron-doped graphene as am etal-free NRR catalyst under ambient conditions.…”
mentioning
confidence: 99%